Konseling Kelompok sebagai Upaya Meningkatkan Efektivitas Pelaksanaan Bimbingan Kepribadian Klien Pemasyarakatan (Studi Kasus di Balai Pemasyarakatan Kelas 1 Jakarta Barat) (Postulat, 2023)
The Community Counselor is a functional official of the Correctional Center whose one of his duties is to carry out community guidance for Correctional Inmates who have served 2/3 of the total criminal period. This study discusses the group counseling method as an effort to increase the effectiveness of Community Counselors in guiding Correctional Inmates who have changed their status to Correctional Clients at the Correctional Center. This study uses a qualitative descriptive approach to the case study, by taking the object of research at the Class 1 West Jakarta Social Center. The results showed that the Group Counseling method had met the formal requirements, namely the formation of a group counseling implementation team. Group Counseling is also considered successful and effective in reducing anxiety and despair in Correctional Clients at the Class 1 Correctional Institution in West Jakarta.